ANALISIS PERANAN KATEGORI EKONOMI BASIS DAN EFISIENSI PERTAMBAHAN INVESTASI DI KABUPATEN MINAHASA UTARA - Julio Patrice Deo Ratag; Vicky V. J. Panelewen; Benu Olfie L. S. (Sam Ratulangi University, 2018)
This research aims to analyze the role of the categorical or economic base sector as well as to observe the efficiency of investment accumulation in North Minahasa Regency. This research was conducted in the area of North Minahasa Regency, North Sulawesi Province. The study began in April until October 2018. This research was conducted in the area of North Minahasa Regency, North Sulawesi Province. The study began in April until October 2018. This research employs secondary data from Regional Gross Domestic Product (RGDP) based on the constant price in North Minahasa Regency and North Sulawesi Province and the data from The Change of Regional Gross Fixed Capital in North Minahasa Regency. The instrument used in this research is Location Quotient (LQ), Shift Share Analysis, and Incremental Capital Output Ratio. Results from LQ show that the category of agriculture, forestry, and fishery, mining and excavation, manufacture, construction, electricity and gas, real estate and education service serve the base category in North Minahasa Regency, with the value of LQ above 1. The role of base category shows positive result towards the formation of the Regional Gross Domestic Product in North Minahasa Regency, agriculture and forestry and fishery are the biggest contributor in RGDP of North Minahasa Regency during the period of 2013-2017. The role of base category through regional share towards North Sulawesi Province also shows positive results, thus base category in North Minahasa Regency contributes to the formation of RGDP in North Sulawesi Province. In the calculation of proportional shift, several base categories in North Minahasa Regency received negative values, namely agriculture, forestry and fishery, manufacture, and education service. Then, in the calculation of differential shift, electronics and gas is the only sector which receives negative value or is not able to compete with similar category in the provincial level. Also, the calculation of Incremental Capital Output Ratio as the instrument of the efficiency of capital income in North Minahasa Regency in the period of 2013-2017 which is calculated by the standard method to lag0, lag1 as well as the mean calculation method, show the result of ICOR which can be categorized as not efficient.